2005
DOI: 10.1590/s0066-782x2005001500005
|View full text |Cite
|
Sign up to set email alerts
|

Tendência da mortalidade por doenças isquêmicas do coração na cidade de Curitiba - Brasil, de 1980 a 1998

Abstract: The study demonstrates a trend of reduction of mortality due to ischemic heart diseases, in both sexes, in the city of Curitiba, from 1980 to 1998. In acute myocardial infarction, such reduction has been happening in a more pronounced way among men, achieving stability, from 60 years of age, among women. The reasons for differentiated reduction trend between sexes are not clear, remaining as na important matter for new investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
1
0
0
2
Order By: Relevance
“…Several studies have demonstrated that the CbVD show a significant increase in mortality with age, reaching very high values in individuals aged above 60 years [22][23][24] , and this has also been confirmed by this study in the city of Londrina. A significant reduction in CbVD mortality rates leads us to infer that the care provided by the Family Health Program in the municipality, which has hypertension as a priority area of the program for the action of health care teams (through the distribution of medications, blood pressure control, and clinical and laboratory monitoring of patients), has contributed to the reduction in mortality rates among women and the elderly.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have demonstrated that the CbVD show a significant increase in mortality with age, reaching very high values in individuals aged above 60 years [22][23][24] , and this has also been confirmed by this study in the city of Londrina. A significant reduction in CbVD mortality rates leads us to infer that the care provided by the Family Health Program in the municipality, which has hypertension as a priority area of the program for the action of health care teams (through the distribution of medications, blood pressure control, and clinical and laboratory monitoring of patients), has contributed to the reduction in mortality rates among women and the elderly.…”
Section: Discussionsupporting
confidence: 89%
“…No caso da doença isquêmica do coração, é possível que o controle de fatores de risco entre homens e mulheres seja ainda mais diferenciado. Tradicionalmente, os homens apresentam maior risco por buscarem cuidados médicos mais tardiamente ou mesmo ignorarem os sintomas 23 .…”
Section: Discussionunclassified
“…Em relação à diminuição percentual das taxas de mortalidade, verificou-se na presente pesquisa que houve uma redução maior no gênero feminino quando analisados os coeficientes padronizados; essa redução percentual foi mais evidente para as DIC. Estudo de tendência de mortalidade por DIC realizado na cidade de Curitiba descreve que nas doenças isquêmicas o gênero feminino apresentou uma queda maior que o masculino 20 . Vários fatores de risco para as DCV, conhecidos globalmente são: pressão arterial elevada (responsável por 13% das mortes no mundo), tabagismo (9%), altos níveis de glicose sanguínea (6%), inatividade física (6%) e sobrepeso e obesidade (5%), entre outros 21,22 .…”
Section: Discussionunclassified